Autoria em sermões religiosos à luz da perspectiva dialógica da linguagem - Silva , Michel Pratini Bernardo da (2017)
The purpose of this paper is to investigate the authorship in sermons of preachers. Therefore, some questions were stablished in order to guide this research: how does a priest, integrant of Religious institutions derived from the Protestant Reform, is author of his statement immersed in a discursive and ideological field full of others‟ discourse? Which are the linguistic, discursive and enunciatively evidences that unveil his authorship? On this basis, this paper aims to analyze the constitution of authorship in religious sermons of protestant preachers. It aimed in particular to describe, analyze and interpret the linguistic, discursive and enunciatively aspects that reveal the constitution of the authorship in the studied sermons. As methodological and theoretic basis, it can be mentioned the dialogic perspective on the language originated by the book Bakhtin e o Círculo,as well as its discursivestudies. The research was from a qualitative-interpretative nature and it can be classified as a descriptive, explanatory and interpretative study. The corpus is composed by 4 religious sermons of protestant preachers collected on Youtube. However, two of them, produced in religious conferences aimed to different publics, are samples analyzed within this paper. After this stage, they continued to be observed by transcription, description, analysis and interpretation of data in order to reach a conclusion. The results pointed out that the preacher 1 summoned simulations of voices of believers and of Pentecostal and Neo-Pentecostal leaders, with an ironic-comic tone, to deconstruct the concept of faith from Christianity. Amongst stylistic choices that select no construction process of the sermon, we observe terms such as "mystery," "invisible," and "witchcraft." On the other hand, the preacher 2 has conversed repeatedly with biblical discourses, considered in the Christian perspective as a word of God that can not be answered. In the production of the sermon, an authorial instance that uses a tone of rebuke, indoctrination and, at times, threat. Some lexical terms such as "homosexual", "sissies", "bisexuals", "demoniacs" have appeared in the thread of the speech as offensive stylistic choices. In this way, we conclude that the authors/preachers, immersed in a discursive context full of others‟ discourses (OD), while producing their statements, frame and evaluate others discourses (OD) by their “sayings”, while making evaluating stylistic choices and applying (to statements) dialogical criticism nuances, as well as ironic/comic, threatening, reprehensive and other nuances.